2017
DOI: 10.1016/j.rmed.2017.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of LABA/LAMA combination on exercise endurance and lung hyperinflation in COPD: A pair-wise and network meta-analysis

Abstract: This meta-analysis clearly demonstrates that if the goal of the therapy is to enhance exercise capacity in patients with COPD, LABA/LAMA combinations consistently meet the putative clinically meaningful differences for both ET and IC and, in this respect, are superior to their monocomponents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
6

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 35 publications
3
35
0
6
Order By: Relevance
“…The superiority of dual combined long-acting beta-2 agonist and muscarinic antagonist (LABA/LAMA) bronchodilators relative to the individual mono-components is modest at best [90,91]. A systematic review of 99 RCTs indicates that while dual long-acting bronchodilators often reduce dyspnea, increase lung function (improved forced expiratory volume in 1 s, FEV 1 ), and improve quality of life compared to single long-acting bronchodilators or LABA/ inhaled corticosteroid (ICS) combinations [92], these results are not consistent and vary in magnitude.…”
Section: Reducing Lung Hyperinflationmentioning
confidence: 99%
“…The superiority of dual combined long-acting beta-2 agonist and muscarinic antagonist (LABA/LAMA) bronchodilators relative to the individual mono-components is modest at best [90,91]. A systematic review of 99 RCTs indicates that while dual long-acting bronchodilators often reduce dyspnea, increase lung function (improved forced expiratory volume in 1 s, FEV 1 ), and improve quality of life compared to single long-acting bronchodilators or LABA/ inhaled corticosteroid (ICS) combinations [92], these results are not consistent and vary in magnitude.…”
Section: Reducing Lung Hyperinflationmentioning
confidence: 99%
“…Studies have assessed improvements in transition dyspnea index (TDI), endurance capacity at a constant work rate, and inspiratory capacity (IC). A large pair‐wise network meta‐analysis of 8 published and unpublished studies including 6 randomized controlled trials in 1632 patients with moderate to severe COPD showed LABA/LAMA therapy to improve exercise endurance by 60 s in a constant work rate exercise protocol and improve IC by 229 ml compared with placebo (Calzetta et al, 2017). Bronchodilatation reduces the end expiratory lung volume (EELV), breathing starts at a lower point in the pressure‐volume curve, requiring less ventilatory drive and reduced intensity of dyspnea (O'Donnell, Revill, and Webb 2001; O'Donnell, Voduc, Fitzpatrick, & Webb, 2004; O'Donnell, Fluge, et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological trials where the statistical significance matches clinical provide the greatest probability that the investigated treatment will be effective in clinical practice . Interestingly, the concept of MCID has been only recently investigated in meta‐analyses in human respiratory medicine . The MID based on change in R L can be used in pharmacological trials to identify responder asthmatic horses to a bronchodilator agent and this approach will permit deep analyses of results beyond the usual comparison of groups .…”
Section: Discussionmentioning
confidence: 99%